Assessment of Land Quality for Siamese Orange (Citrus nobilis var. microcarpa) Development in Pacitan Regency, Indonesia - Rahayu Rahayu; Supriyadi Supriyadi; Sumani Sumani; Aktavia Herawati; Kurnia Mukti Dewi; Yang Geun Mo; Eun Ji Bae (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2024)
Siamese oranges are one of the most widely developed horticultural crops in Indonesia. Arjosari and Ngadirojo are some of the sub-districts that produce Siamese orange in Pacitan Regency. One of the factors that can affect the development of citrus is land quality. This study aims to obtain land quality index data and improvement efforts for developing Siamese orange. Soil samples were taken from 25 land mapping units (LMUs) with 87 sample points. The soil sampling points were determined based on area or sampling density. Data analysis used for soil quality assessment includes correlation, principal component analysis (PCA), minimum data set (MDS), and calculation of climate quality index. The parameters used in this study are bulk density, porosity, moisture content, texture, pH, electrical conductivity (EC), cation exchange capacity (CEC), base saturation, total N, available P, available K, soil organic carbon (SOC), microbial biomass carbon (MBC), evapotranspiration, temperature, and solar radiation. Based on the results of soil quality analysis in the study area, it has a value range of 0.28 to 0.37, including low class, while the climate quality index is 1.39 with moderate class. The land quality index has a very low to low class with a value of 0.39 to 0.51. Intrinsic, extrinsic, and anthropogenic factors can influence soil quality. The study area’s limiting factors for developing Siamese oranges are EC, total N, and available P, which can be improved by making furrow ponds, adding organic fertilizer, using urea fertilizer, and SP36 according to the dosage.